Comparison of Evaluation Approaches: Tests and Non-Tests on Students' Critical Thinking at SMPN 1 Wera - Ajwar, muhammad; Suastika, I Nengah (JUPE : Jurnal Pendidikan Mandala, 2024)
This research is motivated by the importance of critical thinking skills in facing the challenges of the 21st century. The 2013 curriculum in Indonesia has emphasized the development of these competencies, but its implementation faces challenges in effective evaluation. This research aims to evaluate the effectiveness of test and non-test approaches in developing students' critical thinking skills at SMP N 1 Wera. The research results show that non-test approaches, such as projects and group discussions, have a significant positive impact on the development of students' critical thinking skills. Students feel more involved and motivated in learning when evaluated with a non-test approach. This approach gives them the opportunity to develop creativity, collaboration, and problem solving, which are important aspects of critical thinking skills. Although there are challenges in implementing non-test approaches, such as lack of time and resources, the benefits far outweigh the barriers. This research concludes that the non-test evaluation approach has great potential in improving student learning and developing critical thinking skills at SMP N 1 Wera.